Monitoramento de um wetland construído de fluxo vertical e leito parcialmente submerso utilizado no tratamento do efluente de um restaurante universitário - Colito, Pedro Monteiro (2017)
The present study aims to evaluate the efficiency of a vertical flow constructed wetland system with partially submerged bed (VFCW), planted with Heliconia rostrata used in the treatment of the effluent produced by a university restaurant located on the Londrina campus of The Federal University of Technology - Parana (UTFPR). The monitoring has been supervised for 10 weeks in a VFCW with 1m2 of surface area, with bed media’s bottom saturation height of 0.25m and fed with two daily loads of 25L / min totalizing a flow rate of 50L / d. After the monitoring period, the results showed average removal efficiencies of 88.58% of Total Nitrogen (TN), 99.37% of Phosphate (PO4 -), maximum removal of 99,20% of COD, and averages of 34,40% for Total Solids and 89.68% for Total Suspended Solids respectively. From the obtained data it was possible to evaluate the removal efficiency of the proposed system, proving its viability of implantation as a decentralized wastewater treatment alternative.